World History of Pandemics (Turkey Health Literacy Journal, 2020)
“Those who fail to read history are destined to suffer the repetition of its mistakes”. The study of past pandemics can be useful in more effective action during current pandemic of COVID-19. In this context, the purpose of this article is to briefly review some of the most important and deadly epidemics in human history. Infectious diseases and epidemics have affected societies throughout history and caused permanent changes in the world. Diseases have sometimes turned into major and fatal epidemics due to natural causes and sometimes due to human error. Throughout history, people have different thoughts about epidemics and have resorted to various measures to control epidemics. These measures sometimes arise from religious beliefs and sometimes are based on scientific evidence such as quarantine, vaccination and hygiene. One of the most important results we have achieved in this review is the importance of international cooperation in the fight against the epidemic. Today, international cooperation is of great importance in order to better control the COVID-19 outbreak. One of the other important issues in the fight against the epidemic is the culture and level of health literacy of societies which and plays a vital role in the successful implementation of all measures taken.